Efeito do déficit hídrico na eficiência de herbicidas e nas características bioquímicas de picão-preto - Vitorino, Hermeson dos Santos [UNESP]; Martins, Dagoberto [UNESP]; Marques, Renata Pereira [UNESP]; Garbiate, Marcos Vinicios (My University, 2012)
The objective of this work was to evaluate conditions the effectiveness of acetolactate synthase (ALS) and protoporphyrinogen oxidase (PROTOX) inhibitors in the Bidens pilosa control under two water deficit conditions, as well as to determine the influence of water deficit under the contents of soluble carbohydrates and protein of weed. The experimental design was randomized completely design with the treatments, with four replications, setup in a factorial scheme 4x2, with four herbicides (fomesafen lactofen, chlorimuron-ethyl and imazethapyr), and two water conditions (-0.5 MPa and -0.01MPa). At 7, 14, 21 and 28 days after application (DAA), was assessed visually control efficiency of herbicides. For the determination of organic solutes plants were collected at 24, 48, 72 and 96 hours after application (HAA). Herbicides controlled efficiently plants of B. pilosa, except lactofen, whereas the water deficit affected the efficiency of control of all the herbicides. The soluble carbohydrate content increased with the imposition of water deficit, however, herbicides and water deficit further reduction of soluble proteins in plants of B. pilosa.
Effect of water deficit on the efficiency of herbicides and biochemical characteristics of hair beggarticks
Keywords: Bidens pilosa; Carbohydrates; Protein